KITD816V and JAK2V617F mutations are seen recurrently in hypereosinophilia of unknown significance. Issue 9 (14th August 2015) - Schwaab, Juliana; Umbach, Roland; Metzgeroth, Georgia; Naumann, Nicole; Jawhar, Mohamad; Sotlar, Karl; Horny, Hans‐Peter; Gaiser, Timo; Hofmann, Wolf‐Karsten; Schnittger, Susanne; Cross, Nicholas C.P.; Fabarius, Alice; et al.
<x xml:space="preserve">Abstract</x> Myeloproliferative neoplasms with eosinophilia are commonly characterized by a normal karyotype and remain poorly defined at the molecular level. We therefore investigated 426 samples from patients with hypereosinophilia of unknown significance initially referred for screening of the FIP1L1‐PDGFRA (FP) fusion gene also for KIT D816V and JAK2 V617F mutations. Overall, 86 (20%) patients tested positive: FP+ in 55 (12%), KIT D816V+ in 14 (3%), and JAK2 V617F+ in 17 (4%) patients, respectively. To gain better insight into clinical characteristics, we compared these cases with 31 additional and well‐characterized KIT D816V+ eosinophilia‐associated systemic mastocytosis (SM‐eo) patients enrolled within the "German Registry on Disorders of Eosinophils and Mast cells." Significant differences included younger age, male predominance, and higher eosinophil counts for FP+ cases while abdominal lymphadenopathy, ascites, and serum tryptase levels >100 μg/l were characteristic for those with KIT D816V. Leukocytes, hemoglobin, and splenomegaly did not differ significantly. A median of three additional mutations, most frequently TET2 and SRSF2, were identified in 12/13 KIT D816V+ SM‐eo patients with available material indicating a more complex molecular pathogenesis. Median survival was not reached for FP+ cases but was only 26 and 41 months for KIT D816V+ SM and JAK2 V617F+ MPN‐eo, respectively. Eosinophilia of ≥2 × 109/l was identified as discriminator for inferior survival in KIT D816V+ and/or JAK2 V617F+ patients (median survival 20 months vs. not reached, P = 0.002). Thus, there is a clear prognostic and therapeutic rationale for detection of KIT D816V and JAK2 V617F in the diagnostic work up of eosinophilia. Am. J. Hematol. 90:774–777, 2015. © 2015 Wiley Periodicals, Inc.